CD40 ligand and MHC class II expression are essential for human peripheral B cell tolerance - Hervé, Maxime (The Rockefeller University Press, 2007)
Hyper-IgM (HIGM) syndromes are primary immunodeficiencies characterized by defects of class switch recombination and somatic hypermutation. HIGM patients who carry mutations in the CD40-ligand (CD40L) gene expressed by CD4(+) T cells suffer from recurrent infections and often develop autoimmune disorders. To investigate the impact of CD40L–CD40 interactions on human B cell tolerance, we tested by ELISA the reactivity of recombinant antibodies isolated from single B cells from three CD40L-deficient patients. Antibody characteristics and reactivity from CD40L-deficient new emigrant B cells were similar to those from healthy donors, suggesting that CD40L–CD40 interactions do not regulate central B cell tolerance. In contrast, mature naive B cells from CD40L-deficient patients expressed a high proportion of autoreactive antibodies, including antinuclear antibodies. Thus, CD40L–CD40 interactions are essential for peripheral B cell tolerance. In addition, a patient with the bare lymphocyte syndrome who could not express MHC class II molecules failed to counterselect autoreactive mature naive B cells, suggesting that peripheral B cell tolerance also depends on major histocompatibility complex (MHC) class II–T cell receptor (TCR) interactions. The decreased frequency of MHC class II–restricted CD4(+) regulatory T cells in CD40L-deficient patients suggests that these T cells may mediate peripheral B cell tolerance through CD40L–CD40 and MHC class II–TCR interactions.